Using gamification elements for competitive crowdsourcing: exploring the underlying mechanism. Issue 9 (4th July 2021) - Yang, Congcong; Ye, Hua Jonathan; Feng, Yuanyue
ABSTRACT: Gamification can be an effective mechanism of engaging individual users (i.e. solvers) in task solving on competitive crowdsourcing platforms. However, past literature lacks a nuanced understanding of how gamification elements can affect solvers' crowdsourcing behaviour via intrinsic and extrinsic motivations. We conceptualised two typical gamification elements (points and immediate performance feedback). Borrowing from self-determination theory, we modelled the effects of points and immediate performance feedback on both intrinsic and extrinsic motivations that, in turn, affect solvers' crowdsourcing participation. Using a survey data of 295 solvers from a large competitive crowdsourcing platform in China, we found that points are positively related to intrinsic and extrinsic motivations, while immediate performance feedback only enhances intrinsic motivation. Both intrinsic and extrinsic motivations positively affect solvers' crowdsourcing participation. The findings of this study enrich our understanding of the mechanisms of the two gamification elements and provide practical insights on how to enhance solvers' participation in crowdsourcing.